2017
DOI: 10.1007/s00394-017-1542-8
|View full text |Cite
|
Sign up to set email alerts
|

Decaffeinated green and black tea polyphenols decrease weight gain and alter microbiome populations and function in diet-induced obese mice

Abstract: In summary, both BTP and GTP induced weight loss in association with alteration of the microbiota and increased hepatic AMPK phosphorylation. We hypothesize that BTP increased pAMPK through increased intestinal SCFA production, while GTPs increased hepatic AMPK through GTP present in the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
115
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(130 citation statements)
references
References 37 publications
12
115
2
1
Order By: Relevance
“…Consistent with our data, other studies have shown that many plant extracts rich in catechins and methylxanthines, like guarana, may activate AMPK concomitantly with reducing weight (Henning et al, ) and increase energy expenditure (Yoneshiro et al, ). Interestingly, when administered together, catechin and caffeine increase energy expenditure in subjects with metabolically active BAT but not in subjects with negligible activity (Yoneshiro et al, ), suggesting that the anti‐obesity effect of catechin and caffeine occurs via BAT activation.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our data, other studies have shown that many plant extracts rich in catechins and methylxanthines, like guarana, may activate AMPK concomitantly with reducing weight (Henning et al, ) and increase energy expenditure (Yoneshiro et al, ). Interestingly, when administered together, catechin and caffeine increase energy expenditure in subjects with metabolically active BAT but not in subjects with negligible activity (Yoneshiro et al, ), suggesting that the anti‐obesity effect of catechin and caffeine occurs via BAT activation.…”
Section: Discussionsupporting
confidence: 93%
“…However, there has been a lack of conclusive data on the specific phylum(s) of microbiota that was responsible for the anti‐obesity effect observed in these previous studies. For instance, some studies reported that F/B ratio was downregulated by polyphenols or Chinese herbal extracts with anti‐obesity bioactivity, while the protective effect of berberine against HFD‐induced obesity was not associated with any significant change of F/B ratio . In the current study, NLE treatment helped to maintain the F/B ratio at a level similar to that of the NCD group, which might contribute to its anti‐obesity effect.…”
Section: Discussionmentioning
confidence: 43%
“…Emerging evidence supports the benefits of a favorable profile of GM in weight management . Many natural products, including plant foods and phytochemicals, have been found to be effective in weight management by modulating GM . However, there has been a lack of conclusive data on the specific phylum(s) of microbiota that was responsible for the anti‐obesity effect observed in these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Eubacterium is involved in cholesterol and bile acid metabolism pathways and can produce butyrate . One of the potential mechanisms between microbiota and weight control might be the fermentation of polysaccharides to SCFAs . In our previous study conducted in vitro , a higher concentration of SCFAs, compared to the control, was observed in the cultures with oolong tea polyphenols .…”
Section: Resultsmentioning
confidence: 92%